BCG Against SARS-CoV-2: Second Youth of an Old Age Vaccine? - Kamat, Siya; Kumari, Madhuree (Frontiers in Pharmacology, 2020)
The sudden outbreak of pandemic COVID-19 caused by SARS-CoV-2 has put the whole world into a difficult situation asking for the immediate development of therapeutics and vaccines against it. Bacillus Calmette–Guérin (BCG), an attenuated strain of Mycobacterium bovis has been administered since decades in many countries against tuberculosis. Today, when a solution against SARS-CoV-2 is urgently needed, the BCG vaccine has again come into the limelight owing to its earlier prevention of non-specific diseases. Data suggest a higher mortality rate of COVID-19 in the non-BCG vaccinated countries, whereas the nations opting for BCG immunization have comparatively lower mortality rate. BCG vaccine is known to induce ‘trained immunity’ and generate ‘non-specific’ heterologous immune responses. It can confer anti-viral immunity by eliciting production of pro-inflammatory cytokines, IL-6, TNF-α, IFN-γ and IL-1β. Though the initial results look promising, a long trail is still to be followed to avoid false promises. The accuracy of nation-wide data, the role of an already activated immune system against ‘cytokine storm’, optimization and timing of vaccine dosage and balancing demand-supply are some of the relevant questions that must be answered before reaching a final conclusion.